PENGARUH RATA-RATA UPAH INDUSTRI DAN TINGKAT PENDIDIKAN TERHADAP PENYERAPAN TENAGA KERJA PADA SEKTOR INDUSTRI MANUFAKTUR DI PROVINSI RIAU - Saddiah Halimahtus; Isyandi H. B; Maulida Yusni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of the average industrial wage and education level on labor absorption in the manufacturing industry sector in Riau Province, and this study also aims to determine which factors have the greatest influence on employment in the manufacturing industry sector in Riau Province. The data used is time series data for the period 2006-2020. The data used in this study is time series data from 2006-2020, sourced from the Central Statistics Agency (BPS). The independent variable in this study is the Manufacturing Industry Average Wage (X1) and Education Level (X2) as seen from the Average Years of Schooling (RLS), while the dependent variable is Labor Absorption in the Manufacturing Industry Sector (Y). The analytical method used in this research is multiple linear regression method with the help of SPSS version 23.0 application. The results of the study indicate that partially the average wage of the manufacturing industry has an effect on employment in the manufacturing industry sector in Riau Province with tcount > ttable i.e. 7,573 > 2,179, while the level of education has no effect on employment in the Manufacturing industry in Riau Province with tcount < t table ie 1.255 < 2.179. The biggest factor influencing employment in the manufacturing industry sector in Riau Province is the average industrial wage variable with a probability value (sig) of 0.000 <0.233. Simultaneously, the average industrial wage and education level have an effect on the employment of the manufacturing industry in Riau Province in 2006-2020 with an Adjusted R2 of 92.9% while 7.1% is influenced by other factors not examined.Keywords: employment in the manufacturing sector and wages in the manufacturing industry